(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Present study was aimed to study phytochemical study for qualitative screening of Martynia annua Linn. and Tephrosia purpurea Linn. for chemical constituents. Extraction of aerial parts of T. purpurea and M. annua leaves was performed by using ethyl alcohol, ethyl acetate, chloroform and petroleum ether. Flavonoid rich extracts of M. annua and T. purpurea was obtained from ethyl alcohol extract. Selected flavonoid rich fraction of both plant was further assess by thin layer chromatography for the pattern of chemical constituents. After development of solvent system both fractions was used for high performance thin layer chromatography (HPTLC). Results were confirmed that percent yield of fractions were calculated as 56.1%w/w (TP-A) and 4.2%w/w (MA-C). Both fraction was confirmed the presence of quercetin. In conclusion both plants and T. purpurea and M. annua extract contains quercetin as 66.35 mg and 28.42 mg, respectively determined by HPTLC method. These two plants are rich source of flavonoids that may be useful for treatment of various diseases.